Genetic parameters of methane emissions determined using portable accumulation chambers in lambs and ewes grazing pasture and genetic correlations with emissions determined in respiration chambers1. (7th May 2018) - Jonker, Arjan; Hickey, Sharon M; Rowe, Suzanne J; Janssen, Peter H; Shackell, Grant H; Elmes, Sarah; Bain, Wendy E; Wing, Janine; Greer, Gordon J; Bryson, Brooke; MacLean, Sarah; Dodds, Ken G; et al.
Abstract: Methane (CH4 ) emission traits were previously found to be heritable and repeatable in sheep fed alfalfa pellets in respiration chambers (RC ). More rapid screening methods are, however, required to increase genetic progress and to provide a cost-effective method to the farming industry for maintaining the generation of breeding values in the future. The objective of the current study was to determine CH4 and carbon dioxide (CO2 ) emissions using several 1-h portable accumulation chamber (PAC ) measurements from lambs and again as ewes while grazing ryegrass-based pasture. Many animals with PAC measurements were also measured in RC while fed alfalfa pellets at 2.0 × maintenance metabolizable energy requirements (MEm). Heritability estimates from mixed models for CH4 and CO2 production (g/d) were 0.19 and 0.16, respectively, when measured using PAC with lambs; 0.20 and 0.27, respectively, when measured using PAC with ewes; and 0.23 and 0.34, respectively, when measured using RC with lambs. For measured gas traits, repeatabilities of measurements collected 14 d apart ranged from 0.33 to 0.55 for PAC (combined lambs and ewes) and were greater at 0.65 to 0.76 for the same traits measured using RC. Genetic correlations ( r g ) between PAC in lambs and ewes were 0.99 for CH4, 0.93 for CH4 + CO2, and 0.85 for CH4 /(CH4 + CO2 ), suggesting that CH4 emissions in lambs and ewes are the same trait. Genetic correlations between PAC and RC measurements were lower, at 0.62 to 0.67 for CH4 and 0.41 to 0.42 for CH4 + CO2, likely reflecting different environmental conditions associated with the protocols used with the 2 measurement methods. The CH4 /(CH4 + CO2 ) ratio was the most similar genetic trait measured using PAC (both lambs and ewes, 63% and 66% selection efficiency, respectively) compared with CH4 yield (g/kg DMI) measured using RC. These results suggest that PAC measurements have considerable value as a rapid low-cost method to estimate breeding values for CH4 emissions in sheep.